Low temperatures induce rapid changes in chromatin state and transcript levels of the cereal VERNALIZATION1 gene - Oliver, Sandra N (Journal of experimental botany, 2013)
Transcriptional activation of the VERNALIZATION1 gene mediates the acceleration of flowering by prolonged cold (vernalization) in temperate cereals. This study examined the earliest stages of the transcriptional response of VRN1 to low temperatures. Time-course analyses, using a sensitive quantitative PCR assay, showed that in sprouting barley seedlings VRN1 transcripts begin to accumulate within 24 hours of the onset of cold. The kinetics of the initial transcriptional response of VRN1 to cold was similar to the cold-induced genes DEHYDRIN5 (DHN5) and COLD REGULATED 14B (COR14B), but occurred at lower levels compared to cold acclimation genes or the response to longer cold treatments. Temperatures between 15 and -2 °C induced expression of VRN1 within 24 hours, with a maximal response observed between 2 and -2 °C. Transcriptional induction was also observed in undifferentiated callus cells. There were significant increases in histone acetylation levels at the VRN1 locus in response to 24-hour cold treatment. Sodium butyrate, a histone deacetylation inhibitor, triggered an increase in histone acetylation at VRN1 chromatin and elevated VRN1 transcript levels. The transcriptional response of VRN1 to short-term cold treatment was examined in near-isogenic lines that have different VRN1 genotypes, showing that an allele of the barley VRN1 gene with an insertion in the first intron and high basal expression levels has a reduced transcriptional response to short term cold treatment. This study suggests that low-temperature induction of VRN1 is a cellular response to cold triggered by the same mechanisms that mediate low-temperature induction of cold acclimation genes